Tendencias de la bioantropología y un estudio de caso : su desarrollo académico en la Universidad del Cauca (2012)
ABSTRACT: Starting with the origins of physical (biological) anthropology, its trends and contents, the authors proposed the term bioanthropology to include a broader meaning which highlights its interdisciplinary profile and the use of mixed methods of research. To illustrate the development of such trends in Colombia, the history of the discipline at the University of Cauca as a case study is shown, reconstructing the beginning, and analyzing the dynamics of teaching and research in bioanthropology based on: academic programs since 1973, interviews with professors and some elements of the Elizabeth Tabares’ autoethnography. It also emphasizes the position of biomedical anthropology in Colombian Pacific populations developed by the University of Cauca.